Strategi Kepala Sekolah dalam Meningkatkan Kualitas Layanan Pendidikan Melalui Gaya Servant Leadership - Muhammad Ramzy Ramadhan; Marhamah Salsabila; Hasyim Asy'ari (UMSU, 2023)
To achieve the quality of education services at the national level, a strategy is needed by the school principal. Principal leadership expects to be able to realize educational goals effectively and efficiently. School principal leadership is when it can mobilize the organization's human resources (educators, school employees, students) to carry out their respective duties and jobs. An appropriate approach to educational institutions needs to move the organizational components, namely the servant leadership style. This research was conducted with a qualitative approach, as for the research method, namely interviews by taking the results of answers from respondents (principals) as individual opinions and then aligned with theoretical studies sourced from library data. In supporting the correctness of this data, it is supported by data reduction techniques, namely analyzing, selecting, and discarding to obtain verifiable conclusions. The study results show six servant leadership models: Value people, develop people, build community, display authenticity, provide leadership, and share leadership. Moreover, the characteristics of servant leadership: listening, fulfilling, empathy, healing, self-awareness, persuasion, and conceptualization.